Spatially selective photoconductive stimulation of live neurons - Campbell, Jacob; Singh, Dipika; Hollett, Geoffrey; Dravid, Shashank M.; Sailor, Michael J.; Arikkath, Jyothi (Frontiers in Cellular Neuroscience, 2014)
Synaptic activity is intimately linked to neuronal structure and function. Stimulation of live cultured primary neurons, coupled with fluorescent indicator imaging, is a powerful technique to assess the impact of synaptic activity on neuronal protein trafficking and function. Current technology for neuronal stimulation in culture include chemical techniques or microelectrode or optogenetic based techniques. While technically powerful, chemical stimulation has limited spatial resolution and microelectrode and optogenetic techniques require specialized equipment and expertise. We report an optimized and improved technique for laser based photoconductive stimulation of live neurons using an inverted confocal microscope that overcomes these limitations. The advantages of this approach include its non-invasive nature and adaptability to temporal and spatial manipulation. We demonstrate that the technique can be manipulated to achieve spatially selective stimulation of live neurons. Coupled with live imaging of fluorescent indicators, this simple and efficient technique should allow for significant advances in neuronal cell biology.